Analysis and DNA interaction of the profluralin herbicide - Morawska, Kamila; Jedlinska, Katarzyna; Smarzewska, Sylwia; Metelka, Radovan; Ciesielski, Witold; Guziejewski, Dariusz (Springer, 2019)
The increasing use of pesticides is a major health issue. There is therefore a need for improved analytical methods and more knowledge on the interaction of pesticides with living organisms. Here, we developed the analysis of profluralin in water and soils by cyclic voltammetry, square-wave voltammetry and square-wave adsorptive stripping voltammetry. We also studied the interaction between profluralin and double-stranded DNA. Results of cyclic voltammetric studies indicate that the reduction processes have an irreversible and adsorption-like character, as a possible consequence of the reduction of nitro groups of profluralin. Quantification was found linear from 60 to 800 nmol L-1 with a detection limit of 17 nmol L-1 using square-wave adsorptive stripping voltammetry. Results of interactions with double-stranded DNA from salmon sperm revealed that profluralin forms a complex with DNA by electrostatic binding. Values of Gibbs free energy confirmed that formation of profluralin-DNA complex is spontaneous and favourable.
Analýza herbicidu profluralin a jeho interakce s DNA
Keywords: profluralin; cetyltrimethylammonium bromide; double-stranded DNA; square-wave adsorptive stripping voltammetry; herbicide; profluralin; cetylmethylammonium bromid; dvojřetězcová DNA; adsorptivní square wave voltametrie; herbicid